Psychological and Sociological Impacts of Male Chauvinism on Women in Beyond The Horizon and So Long A Letter - Lawali, Maman Toukour; Tontoh, Esther (International Journal of Language and Literary Studies, 2025)
This study explores the psychological and sociological impacts of male chauvinism on women in Amma Darko’s Beyond the Horizon and Mariama Bâ‘s So Long a Letter. Using radical feminism and narcissistic theory as lenses, the paper qualitatively employs a textual analysis of the two novels to show how male chauvinism, as a belief that sees men as superior to women, and the oppression and relegation of women in patriarchal African societies, psychologically and sociologically greatly impacts women. The study reveals that emotional trauma, depression, loss of self-esteem, identity crisis, fragmentation of women, deep scars of psychological oppression, male superiority over women, economic disempowerment, and loss of autonomy are the main psychological and sociological impacts on women. The paper concludes by summarizing male chauvinism’s psychological and sociological implications before recommending women’s empowerment in African societies as a shield to male chauvinism.